Creative Placemaking and Social Innovation in Art Education for Transforming Communities in Indonesia and Malaysia - Sampurno, Muchammad Bayu Tejo; Juwariyah, Anik; Djatiprambudi, Djuli; Trisakti, Trisakti; Djahwasi, Herry Rizal; Safian, Abdul Rahman (European Public & Social Innovation Review, 2025)
Introduction: Creative placemaking is a transformative strategy that fosters social cohesion, economic resilience, and cultural sustainability in Indonesia and Malaysia by reclaiming public spaces as sites of collective identity and empowerment. This study examines its impact on urban and rural development, emphasizing the role of art education in sustaining participatory initiatives. Methodology: Ethnographic fieldwork and quantitative analyses in Indonesia (Yogyakarta, Jakarta, Bandung) and Malaysia (Kuala Lumpur, Penang) reveal that artistic interventions strengthen community networks, increase economic opportunities, and promote intergenerational knowledge exchange. However, challenges include inconsistent funding, policy misalignment, and the commercialization of community-driven art. Results: Findings highlight the necessity of interdisciplinary collaborations among artists, educators, and policymakers to sustain creative placemaking. Such efforts are crucial to maintaining its long-term viability. Discussion: Integrating art education within formal and informal learning environments offers a viable model for cultural preservation and creative engagement. As urbanization accelerates in Southeast Asia, creative placemaking must remain dynamic and inclusive, prioritizing artistic integrity and community participation. Conclusion: Policy reforms are essential to ensuring creative placemaking continues as a vehicle for social innovation, cultural heritage preservation, and sustainable development. They will also keep artistic interventions community-driven and responsive to evolving sociocultural landscapes.